1982
DOI: 10.1080/00480169.1982.34882
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of two serotypes of equine adenovirus from horses in New Zealand

Abstract: Two serologically unrelated adenoviruses were isolated from ill-thrifty young horses on a thoroughbred stud. The viruses differed in their cytopathic effects in cell culture and in their haemagglutination properties. A serological survey of horses in the northern half of the North Island showed the prevalence of precipitating antibodies against equine adenoviruses to be 39%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…EAdV2 primers did not amplify a PCR product from a New Zealand EAdV isolate that was not neutralised by EAdV1 antiserum. 13 Accordingly this virus may represent a third EAdV type.…”
Section: Scientific Eadv1 and Eadv2mentioning
confidence: 99%
“…EAdV2 primers did not amplify a PCR product from a New Zealand EAdV isolate that was not neutralised by EAdV1 antiserum. 13 Accordingly this virus may represent a third EAdV type.…”
Section: Scientific Eadv1 and Eadv2mentioning
confidence: 99%
“…EAdV-1 is ubiquitous in horses and readily isolated from both healthy horses and horses with clinical signs [7,11]. Since a 24.1% EAdV-1 seroprevalence was first reported in British horses [13], several serological studies have been conducted in various countries with reported seroprevalence findings of 82.7% and 8.6% in Japan [14,15], 54.9% and 77% in Australia [6,16], 39.9% and 91.3%% in New Zealand [17,18], 10.6% in Ireland [19], 4.5% in Nigeria [20], and 39.0% in the Netherlands [21]. A polymerase chain reaction (PCR) assay is an important method in EAdV-1 diagnosis, and PCRs targeting the EAdV-1 hexon gene have been commonly used in previous studies [10,12,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Adenoviruses are nonenveloped, icosahedral, double-stranded DNA viruses (Shenk 2001) that cause a variety of diseases in different animal species, including respiratory, enteric and disseminated infections that often are most severe in neonates (Cole 1971;Abzug and Levin 1991;Kolavic-Gray et al 2002;Boomkens et al 2004). Two equine adenoviruses (EAdV1 and 2) have been identified: EAdV2 has been isolated from the lymph nodes and faeces of foals with upper respiratory tract disease and diarrhoea (Horner and Hunter 1982;Studdert and Blackney 1982), whereas EAdV1 has been isolated worldwide from nasopharyngeal secretions of foals and horses with and without disease (Studdert et al 1974). EAdV1 causes fatal pneumonia in Arabian foals with severe combined immunodeficiency (SCID; Studdert 1978) and, possibly, in Fell pony foals with an undefined immunodeficiency (Richards et al 2000).…”
Section: Introductionmentioning
confidence: 99%